Organizational research methods : a guide for students and researchers - Brewerton, Paul.; Millward, Lynne (London ; Thousand Oaks, Calif. : SAGE, 2001)
This book provides the reader with clear pointers for how to conduct organizational research appropriately, through planning and making informed and systematic research decisions, to understanding the ethical implications of applied organizational research, to implementing, reporting and presenting the findings to the highest possible standards.
Cover; Contents; List of Figures; List of Tables; List of Boxes; List of Case Studies; Preface; Chapter 1 -- Introduction; Chapter 2 -- Applying Social Science to the Real World; Chapter 3 -- Starting off the Research Process; Chapter 4 -- Obtaining and Using Access to an Organization; Chapter 5 -- Project Design; Chapter 6 -- Methods of Data Collection; Chapter 7 -- Sampling Considerations; Chapter 8 -- Assessing Performance in Organizations; Chapter 9 -- Data Analysis; Chapter 10 -- Reporting Research Findings; Chapter 11 -- Concluding Words; Glossary; Index.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Organizational sociology -- Research; Organization -- Research -- Methodology; Organizational behavior -- Research; Sociologie des organisations -- Recherche; Organisation -- Recherche -- Méthodologie.; Comportement organisationnel -- Recherche; Organisation -- Recherche; BUSINESS & ECONOMICS -- Negotiating; Organization -- Research -- Methodology; Organizational behavior -- Research; Organizational sociology -- Research; Einführung; Forschungsmethode; Methode; Organisation; Organisationspsychologie; Organisatieonderzoek; Onderzoeksmethoden; Einführung.